CONSTIPATION SYNDROME IN CHILDREN - Сарычева, Елена Германовна; Любова, Наталья Сергеевна (Mother and Baby in Kuzbass, 2022)
The purpose of the study is to conduct a clinical and morphological study of patients with constipation syndrome, who are on a gastroenterological bed in a pediatric hospital, in order to identify both functional and organic lesions of the digestive system.Materials and research methods. A total of 724 children aged 0 to 16 years old were examined according to a single algorithm. Of these, the main study group consisted of 412 patients with constipation syndrome, the control group – 312 children (without constipation).Conclusions. As a result of the conducted studies, it was possible to find out that subatrophy develops in children with constipation syndrome in histological studies. Constipation syndrome in children is a very urgent problem that requires further research, understanding, obtaining new data, especially endoscopic and morphological data for improving therapeutic programs, requiring an individual approach.
Keywords: constipation; stone smearing; defecation; subatrophy of the colon mucosa; children